The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1091/mbc.7.7.1043
|View full text |Cite
|
Sign up to set email alerts
|

Genes that control the fidelity of endoplasmic reticulum to Golgi transport identified as suppressors of vesicle budding mutations.

Abstract: Although convergent evidence suggests that proteins destined for export from the endoplasmic reticulum (ER) are separated from resident ER proteins and are concentrated into transport vesicles, the proteins that regulate this process have remained largely unknown. In a screen for suppressors of mutations in the essential COPII gene SEC13, we identified three genes (BST1, BST2/EMP24, and BST3) that negatively regulate COPII vesicle formation, preventing the production of vesicles with defective or missing subun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
161
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(170 citation statements)
references
References 48 publications
9
161
0
Order By: Relevance
“…Deletion of EMP24 or ERV25 suppresses the sec13-1 temperature-sensitive mutation and even bypasses a complete deletion of SEC13 (7). As an additional test of function, we found that the ⌬24-EME mutation did not suppress sec13-1 as ex- FIG.…”
Section: Coat Binding Properties Of the Emp24p And Erv25pmentioning
confidence: 77%
See 3 more Smart Citations
“…Deletion of EMP24 or ERV25 suppresses the sec13-1 temperature-sensitive mutation and even bypasses a complete deletion of SEC13 (7). As an additional test of function, we found that the ⌬24-EME mutation did not suppress sec13-1 as ex- FIG.…”
Section: Coat Binding Properties Of the Emp24p And Erv25pmentioning
confidence: 77%
“…Previous studies showed that deletion of EMP24 bypassed the requirement for SEC13 (7). Therefore, we crossed the sec13-1 mutation into our strains and scored for growth at 37°C.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Emp24p, a member of this family, is necessary for efficient packaging of Gas1p into ER-derived vesicles and can be directly cross-linked to Gas1p (61). EMP24 was also identified as a BST2 gene that bypasses the requirement for Sec13p in coat protein complex II (COPII) vesicle formation (62). Recently it was reported that BST1, which also bypasses sec13 mutant, encodes a functional yeast homologue of mammalian GPI inositol deacylase (63).…”
Section: Roles Of Multicopy Suppressors In Gpi7mentioning
confidence: 99%